2021
DOI: 10.3389/fcell.2021.770458
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Disruption of Erbb4 in Pet1+ Neurons Impairs Serotonergic Sub-System Connectivity and Memory Formation

Abstract: The serotonergic system of mammals innervates virtually all the central nervous system and regulates a broad spectrum of behavioral and physiological functions. In mammals, serotonergic neurons located in the rostral raphe nuclei encompass diverse sub-systems characterized by specific circuitry and functional features. Substantial evidence suggest that functional diversity of serotonergic circuits has a molecular and connectivity basis. However, the landscape of intrinsic developmental mechanisms guiding the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Testing apparatuses were cleaned with a solution of 70% ethanol in water after each trial to avoid olfactory cues. Behavioral tasks were recorded and analyzed as previously described 102 . Open field.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Testing apparatuses were cleaned with a solution of 70% ethanol in water after each trial to avoid olfactory cues. Behavioral tasks were recorded and analyzed as previously described 102 . Open field.…”
Section: Methodsmentioning
confidence: 99%
“…The arena was delimited for analysis into two different regions: center (square area of 30 × 30 cm equidistant from the walls) and the remaining borders. The time spent, velocity, distance as well as transitions between the zones was calculated as described in 102 . Elevated plus maze.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In rodents, part of PFC development occurs during the first three postnatal weeks, when layer 5 neurons exhibit high intrinsic excitability and enhanced rates of synaptogenesis [3][4][5][6] . Studies carried out in this phase identified that excitatory activity leads to the building of new synaptic connections and reorganization of cortical circuits, with critical consequences in adult behavioral phenotype [7][8][9][10][11][12] . According to these findings, prefrontal neurons undergo a temporal window of higher synaptic modifications in early life.…”
mentioning
confidence: 99%